Nutritional Content of Tembakul Fish (Periophtalmodon Schlosseri) in Ratulodong Village, East Flores Regency - Labi , Yulius Carlos; Batafor , Yosephina M.J; Larantuka , Karolus Banda (Global Education Journal, 2025)
The Java sparrow is a unique fish species because it can live in two different habitats, on land and at sea. Java sparrow (Periophtalmodon schlosseri) often spends its time outside the water and uses mangrove forests as its habitat. The abundance of Java sparrow (Periophtalmodon schlosseri) in East Flores Regency allows for in-depth research on the nutritional content of Java sparrow. This study aims to determine the nutritional content of Java sparrow in Ratulodong Village. This research method uses a Mixed Research approach with quantitative and qualitative data. The study was conducted in July–August 2024. Samples of fresh Java sparrow (300g) were collected from the mangrove area of ​​Ratulodong Village. Analysis was carried out at the Food Chemistry Laboratory of Nusa Cendana University using the AOAC method (2005). The results of the study showed that the nutritional content testing of the tobacco fish took place in the Food Chemistry Laboratory of the Faculty of Animal Husbandry and Fisheries, Nusa Cendana University, Kupang, by following the procedures of AOAC (Association of Official Analytical Chemists) 2OO5, namely: the kjedahl method for testing protein content, gravimetry for testing water and ash content, soxhlet for testing fat content, by difference method for calculating carbohydrate content. The analysis results obtained from this study were as follows: 80% water, 50.1% protein, 35% ash, 7.1% carbohydrate, 6.1% fat.